A case control study of asymptomatic hyponatremia in patients with chronic kidney disease - Mishra, Aditya K.; Bhatttacharjee, Koushik; Sircar, Dipankar (International Journal of Research in Medical Sciences, 2024)
Background: This study has been conducted to assess the association between asymptomatic hyponatremia with cognitive dysfunction, bone health, quality of life and various inflammatory markers in non-dialysis chronic kidney disease patients. Methods: A single centre hospital based observational case-control study conducted at a tertiary care hospital in eastern India. Non dialysis chronic kidney disease patients with (case) or without (control) asymptomatic hyponatremia were included in the study after proper assessment of inclusion and exclusion criteria. Relevant clinical and laboratory parameters were recorded. C reactive protein and interleukin 6 were measured and T score was assessed by dual-energy X-ray absorptiometry (DEXA) scan at lumbar vertebra (L1 to L4). For cognitive function assessment, Bangla adapted mental state examination (BAMSE) score was calculated and activities of daily living (ADL) score was also recorded. Results: 38 patients in the control group and 37 patients in the case group came for follow-up visit. Significant positive correlation was found between serum sodium levels with the DEXA scan (T-scores). On the other hand, significant negative correlation was found between serum sodium with C-reactive protein (CRP) and interleukin-6 (IL-6) levels. Though BAMSE scores and ADL scores showed a positive correlation with serum sodium levels, the result was not statistically significant. Conclusions: We conclude that asymptomatic hyponatremia in non-dialysis chronic kidney disease patients has significant association between DEXA scan T score and various inflammatory parameters like C reactive protein and interleukin 6. This may indicate possible role of prevention and treatment of this common electrolyte abnormalities to avoid effect of poor bone health and chronic inflammation in such a vulnerable population.